1976
DOI: 10.1055/s-0038-1647919
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Adhesion, Release and Aggregation in Flowing Blood: Effects of Surface Properties and Platelet Function.

Abstract: SummaryPlatelet adhesion to natural and artificial surfaces and adhesion-induced aggregation were investigated in vitro using an annular perfusion chamber. The surfaces were exposed to anticoagulated blood under identical flow conditions (~ arterial shear rates). The initial attachment of platelets (contact) appeared less surface specific than spreading and release. Fibrillar collagen was the most powerful inducer of platelet degranulation whereas elastin, microfibrils and epon were virtually inactive. Fibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

1978
1978
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(98 citation statements)
references
References 20 publications
4
92
0
2
Order By: Relevance
“…Nonetheless, the observations support the theory of platelet depletion from the boundary layer of the blood flow, 59 an effect that is gradually overcome by increasing shear rates that enhance the radial transport of platelets toward the boundary layer and the surface, 625 and that may increase the translocation of platelet masses from upstream to downstream positions. 3 Thus, at low shear rates, the consumption of platelets by growing thrombi exceeds the radial platelet transport toward the boundary layer, while at higher shear rates the consumption is gradually compensated by the net increased flux of platelets to the boundary layer. Reduction of platelet consumption from the boundary layer by partial inhibition of thrombus growth with aspirin, which abolished the axial dependence, further substantiates the proposed physical explanation of axial-dependent platelet-surface interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the observations support the theory of platelet depletion from the boundary layer of the blood flow, 59 an effect that is gradually overcome by increasing shear rates that enhance the radial transport of platelets toward the boundary layer and the surface, 625 and that may increase the translocation of platelet masses from upstream to downstream positions. 3 Thus, at low shear rates, the consumption of platelets by growing thrombi exceeds the radial platelet transport toward the boundary layer, while at higher shear rates the consumption is gradually compensated by the net increased flux of platelets to the boundary layer. Reduction of platelet consumption from the boundary layer by partial inhibition of thrombus growth with aspirin, which abolished the axial dependence, further substantiates the proposed physical explanation of axial-dependent platelet-surface interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The details surrounding the process of platelet activation, adhesion and aggregation can be found in Lasslo (1984), Yamazaki and Mustard (1987) and Anthony Ware and Coller (1995). Macroscopic studies of platelet adhesion, deposition and thrombus formation in annular flow chambers Baumgartner (1973) (or in the stagnation point flow chamber (Affeld et al (1995)) have shown that the rate and extent of platelet adhesion, platelet deposition and platelet thrombus (or mural thrombus) formation are affected by the flow conditions (shear rates) (Weiss et al, 1978;Tschopp et al, 1979;Turitto and Baumgartner, 1979;Turitto et al, 1980; see also Alevriadou et al (1993) for the effect of flow conditions on vWF mediated platelet aggregation), the presence of citrate , and surface properties (Baumgartner et al, 1976;Baumgartner, 1977; see also Hubbell and McIntire, 1986). Platelet activation itself (Kroll et al, 1996;Christodoulides et al, 1999), and sometimes lysis, is known to occur in response to prolonged exposure to high shear stresses (Wurzinger et al, 1985).…”
Section: Platelet Activation Adhesion and Aggregationmentioning
confidence: 99%
“…The presence of fibrin is usually demonstrated by immunofluorescence with the use of radioisotopes or by morphological quantification. 12 -15 Fibrin deposition on subendothelium in flowing blood has been studied in an ex vivo thrombosis model originally developed by Baumgartner et al 3 - 16 - 19 To study the participation of the vessel wall in thrombus formation, our laboratory recently introduced an adapted in vitro thrombosis model that permits studies of thrombus formation in flowing blood on extracellular matrixes of cultured human cells. 20 In both models, the morphometric evaluation of fibrin deposition led to semiquantitative results at best.…”
Section: (Arteriosclerosis and Thrombosis 1991;ll:211-220)mentioning
confidence: 99%
“…Fibrin dep-L osition and platelet aggregation are essential steps in thrombus formation on subendothelial surfaces or perivascular connective tissue. 1 " 3 To what extent fibrin deposition contributes to the formation of the thrombus is influenced by several parameters such as the availability of tissue factor on the vascular surface and local flow characteristics. 4 -5 Fibrin accounts for most of the mass of thrombi found in large veins; such thrombi mainly consist of fibrin and red blood cells.…”
Section: (Arteriosclerosis and Thrombosis 1991;ll:211-220)mentioning
confidence: 99%